Testi, editori e lettori “digitali”. Riflessioni pedagogiche - Di Bari, Cosimo (Studi sulla Formazione/Open Journal of Education, 2014)
In the last decades, marked by the digital technologies, textuality is taking on new forms. The transformations concern books and medias, but also editors and readers: the paper aims to evaluate how pedagogy can interpret these changes and can allow the subject to use these technologies (new forms of books includ- ing) as educational tools.